Aromatic border plants in early season berries do not increase parasitism of spotted wing drosophila, Drosophila suzukii. Issue 1 (10th October 2022) - Tsuruda, Matthew; Girod, Pierre; Clausen, Martina; Carrillo, Juli
Abstract: BACKGROUND: The spotted wing drosophila, Drosophila suzukii Matsumura, is a South‐East Asian vinegar fly that is a serious worldwide economic threat to the small fruit industry. Typical control consists of weekly pesticide applications, which can have nontarget effects, increase residual pesticides and lead to the development of resistance within pest populations. One potential alternate method of control is the planting of aromatic intercrops to attract the natural enemies of D. suzukii and/or repel the flies directly. We intercropped strawberry rows with flowering sweet alyssum or ryegrass‐clover (control) to evaluate their efficacy at mitigating D. suzukii infestation through the attraction of two specialized larval parasitoids, Leptopilina japonica (Novkovic and Kimura) and Ganaspis brasiliensis (Ihering). RESULTS: Our study did not demonstrate any significant effect of sweet alyssum intercropping on the infestation rate of D. suzukii in strawberries or parasitism level. However, we found that advanced sampling date and recorded numbers of D. suzukii larvae and parasitoids were positively correlated, indicating higher populations at the end of the strawberry‐growing season. CONCLUSIONS: Sweet alyssum intercrops did not reduce D. suzukii infestation rates or increase parasitism levels, likely due to low population numbers in early season berry varieties. Aromatic intercrops may be more effective for increasing pest control in later season crops. © 2022 Society of Chemical Industry. Abstract : We found that the inclusion of aromatic intercrops in strawberry fields did not increase the parasitism rate of Drosophila suzukii by two exotic hymenopteran parasitoids or lower infestation levels.